Equilibrium [videorecording (DVD)] - Wimmer, Kurt, 1964-; Bean, Sean; Bale, Christian, 1974-; Diggs, Taye; Watson, Emily, 1967- (Paramount Home Entertainment, 2021)
In a fascist future, emotions are illegal as are all books and forms of art. The populace is subdued by being forced to take an emotion-hindering drug, Prozium. When one of the enforcers of the system misses a dose of Prozium, he fights to overthrow it.